Racial Disparities in Access to Small Business Credit: Evidence from the Paycheck Protection Program - Sabrina T. Howell; Theresa Kuchler; David Snitkof; Johannes Stroebel; Jun Wong (Center for Economic Studies and ifo Institute (CESifo), 2021)
We explore the sources of racial disparities in small business lending by studying the 806 billion Paycheck Protection Program (PPP), which was designed to support small business jobs during the COVID-19 pandemic. PPP loans were administered by private lenders but federally guaranteed, largely eliminating unobservable credit risk as a factor in explaining differential lending by race. We document that even after controlling for a firm's zip code, industry, loan size, PPP approval date, and other characteristics, Black-owned businesses were 12.1 percentage points (70% of the mean) more likely to obtain their PPP loan from a fintech lender than a traditional bank. Among conventional lenders, smaller banks were much less likely to lend to Black-owned firms, while the Top-4 banks exhibited little to no disparity after including controls. We use novel data to show that the disparity is not primarily explained by differences in pre-existing bank or credit relationships, firm financial positions, fintech affinity, or borrower application behavior. In contrast, we document that Black-owned businesses' higher rate of borrowing from fintechs compared to smaller banks is particularly large in places with high racial animus, pointing to a potential role for discrimination in explaining some of the racial disparities in small business lending. We find evidence that when small banks automate their lending processes, and thus reduce human involvement in the loan origination process, their rate of PPP lending to Black-owned businesses increases, with larger effects in places with more racial animus.
Keywords: G21; G23; G28; G41; J15; 330